MODEL SETS BERMUATAN ETNOSAINS: PENGARUHNYA TERHADAP LITERASI SAINS SISWA - Rikizaputra Rikizaputra; Arlian Firda; Fani Rahma Sari (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
This research aims to determine the influence of the SETS (Science Environment Technology Society) learning model containing ethnoscience on students' scientific literacy. Conducted in class X SMA Negeri 2 Pekanbaru for the 2022/2023 academic year. Using experimental research with a randomized pretest posttest control group design. The population in this study was class X with a research sample of students in classes X1 and X2 with a total of 36 students in each class. Samples were taken using simple random sampling technique. Data collection was carried out through pretest, posttest and observation sheets. The research results showed that the average N-Gain in the control class was 0.39 (medium) and the experimental class was 0.59 (medium). The results of the N-Gain t-test showed a significant difference between the experimental class and the control class. Thus, it can be concluded that the use of the SETS learning model containing ethnoscience has a significant effect on students' scientific literacy on ecosystem cocept.